2018
DOI: 10.1177/1756286418775375
|View full text |Cite
|
Sign up to set email alerts
|

MRI features as a helpful tool to predict the molecular subgroups of medulloblastoma: state of the art

Abstract: Medulloblastoma is the most common malignant pediatric brain tumor. Medulloblastoma should not be viewed as a single disease, but as a heterogeneous mixture of various subgroups with distinct characteristics. Based on genomic profiles, four distinct molecular subgroups are identified: Wingless (WNT), Sonic Hedgehog (SHH), Group 3 and Group 4. Each of these subgroups are associated with specific genetic aberrations, typical age of onset as well as survival prognosis. Magnetic resonance imaging (MRI) is performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 67 publications
1
18
0
Order By: Relevance
“…The risk stratification for medulloblastoma was suggested long ago without incorporating genetic findings (Packer et al, 2003). Magnetic resonance (MR) imaging-based signatures were promising in predicting molecular subgroups (Colafati et al, 2018) but have not been used in predicting patient prognosis. Although gene signatures were investigated in several studies, a major focus was on patient preselection for targeted therapy (Shou et al, 2015) or molecular classification (Corno et al, 2012;Chen et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The risk stratification for medulloblastoma was suggested long ago without incorporating genetic findings (Packer et al, 2003). Magnetic resonance (MR) imaging-based signatures were promising in predicting molecular subgroups (Colafati et al, 2018) but have not been used in predicting patient prognosis. Although gene signatures were investigated in several studies, a major focus was on patient preselection for targeted therapy (Shou et al, 2015) or molecular classification (Corno et al, 2012;Chen et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that although maximal safe resection should remain the standard of care, aggressive neuro-surgical removal of small residual portions of medulloblastoma should not be attempted, particularly when the anticipated morbidity is high. Several different studies discussed herein, some of which were summarized in a review previously suggest that MRI features can be a helpful and promising tool for early identification of molecular subgrouping in medulloblastoma with potential to influence therapy [41] . The availability of robust and reliable imagingbased predictors of molecular subgrouping could aid neuro-surgical decision-making.…”
Section: Practical and Clinical Implicationsmentioning
confidence: 99%
“…As a first diagnostic procedure, a cranial CT-Scan is often performed. In the case of medulloblastoma patients, the tumor mass typically appears hyperdense on the CT scan [ 10 , 11 ]. Further diagnostic exams should be carried out after the initial proof of a cerebellar tumorous mass.…”
Section: Diagnostic and Stagingmentioning
confidence: 99%